2016
DOI: 10.1016/j.tranpol.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Just a better taxi? A survey-based comparison of taxis, transit, and ridesourcing services in San Francisco

Abstract: In this study, we present exploratory evidence of how "ridesourcing" services (app-based, ondemand ride services like Uber and Lyft) are used in San Francisco. We explore who uses ridesourcing and for what reasons, how the ridesourcing market compares to that of traditional taxis, and how ridesourcing impacts the use of public transit and overall vehicle travel. In spring 2014, 380 completed intercept surveys were collected from three ridesourcing "hot spots" in San Francisco. We compare survey results with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
531
7
33

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 923 publications
(663 citation statements)
references
References 12 publications
(8 reference statements)
32
531
7
33
Order By: Relevance
“…More specifically, ride-sourcing dynamically matches travel supply and demand by enabling travellers to request car rides in real-time from potential suppliers using a smartphone application [74]. Ride-splitting is an interesting form of ride-sourcing where riders with similar origins and destinations are matched to the same ride-sourcing driver and vehicle in real-time, and the ride and costs are split among users [63,75].…”
Section: Ride-sourcingmentioning
confidence: 99%
“…More specifically, ride-sourcing dynamically matches travel supply and demand by enabling travellers to request car rides in real-time from potential suppliers using a smartphone application [74]. Ride-splitting is an interesting form of ride-sourcing where riders with similar origins and destinations are matched to the same ride-sourcing driver and vehicle in real-time, and the ride and costs are split among users [63,75].…”
Section: Ride-sourcingmentioning
confidence: 99%
“…Specifically, TNC user surveys suggest that, relative to taxi users, TNC passengers are younger and posses a higher average level of education (Rayle et al, 2016). Our work continues on this thread by exploring di↵erences in the types of events that are attended by these two groups of passengers.…”
Section: Introductionmentioning
confidence: 89%
“…1 It has an estimated market value of over $68 billion. 2 In the case of many cities, ride sharing started to be substitute for the traditional taxicab services in the intra-city public transportation. One recent report found that ride sharing met an average 46% of all total paid car rides through Uber in the major US cities in the irst quarter of 2015, 3 because ride sharing is cheaper than a cab trip.…”
Section: The Rise Of Ride Sharing or Invisible Handmentioning
confidence: 99%
“…This refers to economic eiciency considerations under competitive market conditions. Most importantly, this system eliminates the transaction costs of a taxicab market under regulated market conditions [1,2]. Conversely, the failure of traditional taxicab services stems from distortions inherent in a regulatory process.…”
Section: Introductionmentioning
confidence: 99%